Soil core microbial taxa maintain community resistance to drive soil ecosystem multifunctionality under Alternanthera philoxeroides invasion - Lin, Xiao; Zhang, Xinyu; Li, Shujing; Wang, Yongming; Yu, Haiyang; Qin, Wenxiu; Zhang, Jiaoyang (Frontiers in Microbiology, 2025)
Alien plant invasion exerts profound impacts on local ecosystems, like biodiversity, stability, and overall functionality. Understanding the ecological stability of soil microbial communities is essential for elucidating how plant invasions drive changes in soil ecosystem functions. In this study, soil ecosystem multifunctionality (EMF) was examined in relation to the resistance of microbial communities across five Alternanthera philoxeroides–invaded sites (Xiaoxian, Hefei, Tongling, Anqing, and Huangshan) within different ecological functional zones in Anhui Province, China, with contrasting soil properties and environmental conditions. Soil samples were collected from invaded and uninvaded plots, microbial core taxa were identified, and structural equation modeling was applied to examine the relationships among invasion, microbial traits, and ecosystem functions. The results showed that invasion significantly increased soil EMF at Xiaoxian by 34.2% and at Hefei by 24.1%, which was primarily by increasing in nitrogen- and phosphorus-related functions. Bacterial communities exhibited consistently higher resistance than fungal communities, owing to their more complex interaction networks. Core bacterial taxa were positively associated with microbial resistance, supporting nutrient cycling and maintaining ultimately EMF. Structural equation modeling revealed that invasion-driven changes in soil properties influenced EMF indirectly through bacterial community resistance mediated by core microbial taxa. These findings demonstrated that bacterial resistance, underpinned by the stabilizing role of core microbial taxa, played a central role in maintaining EMF during plant invasion. The results highlight the importance of core microbial taxa as ecological stabilizers and provide new insights into the belowground mechanisms linking biological invasions to ecosystem resilience.